Migliora: Terminal year end report - Bactat, Jameson Cinco (Animo Repository, 2023)
Migliora is a sustainable fashion retailing company founded by Lasallian students in the Philippines as part of their course requirement in Entrepreneurship. In Italian, it means "to improve” or “get better,” reflecting the brand's commitment to improving individually and collectively continuously. Migliora specializes in using recycled plastic bottles or rPET as the main fabric for its clothing. After only releasing two product lines (polos & scrunchies), the company has seen overwhelming success. The Terminal Year-End Report Volume 1 summarizes the company’s journey by discussing its objectives, identified opportunities, challenges, significant learnings, and more. Moreover, the Terminal Year-End Report Volume 2 extends the previous report by outlining the critical decisions made for Migliora. This report includes the board resolutions, meeting minutes, publication materials, and financial statements. Lastly, Migliora's business plan is also included, which details the foundation of its operations, such as market research conducted, product specifications, and more. As its simulation process ends, Migliora’s journey is just beginning. The partners plan to continue the company and take it to new heights.